Effect of Diamond and Carbide Burs on Dentinal Tubules and Predentin Diameter - Khan, Nabila Momin; Khan, Muhammad Haroon (Journal of Gandhara Medical and Dental Science, 2022)
OBJECTIVES: To find out the effect of Diamond and Carbide burs on the diameter of dentinal tubules and predentin of premolar teeth. METHODOLOGY: A Laboratory-based experimental study was conducted at the anatomy department, Institute of Basic Medical Sciences, Khyber Medical University, from January 2018 to March 2018. Sixty premolars were obtained from patients considering the inclusion and exclusion criteria. Six teeth were extracted for control group A. Fifty-four maxillary and mandibular premolar teeth in patients underwent cavity preparation carried out by diamond bur (group B) for twenty-seven teeth and other twenty-seven teeth by carbide bur (group C) and were removed from patients at a dental hospital in Peshawar (RCD). They underwent processing and were then stained with Eosin, Hematoxylin and Masson's trichrome to observe the diameter of dentinal tubules and predentin. RESULTS: The dentinal tubules and predentin diameters were observed and measured in all samples in both control group A and experimental groups B and C. No effect was seen in dentinal tubules diameter. In the Control group, the diameter of predentin was less as compared to Experimental groups B and C, i.e., 10-17.5µm in group A whereas the range for Diamond bur (Group B) and Carbide bur (Group C) was 12.5-25µm and 20-37.5µm whereas. CONCLUSION: It was concluded that in comparison with Carbide bur, Diamond bur is more beneficial than Carbide bur as the Diamond bur has no effect on dentinal tubules diameter whereas little effects on predentin diameter.